The Sustainability of health care systems in Europe - Baltagi, Badi H. (Badi Hani); Moscone, Francesco (Contributions to economic analysis, 2021)
This volume contains an Open Access Chapter - This book provides a comprehensive understanding of the sustainability of health systems in Europe. Furthermore, it includes an introduction on how EU action in supporting health- care policies in the EU Member States, both looking at implemented actions and describing current priorities for the future.